Clinical use of fluvoxamine in women with major depression during the menopausal period – The evaluation of therapeutic effect and safety - Lipińska-Szałek, Agata; Krogulski, Sławomir (Menopause Review/Przegląd Menopauzalny, 2002)
Aim of the study: To evaluate the therapeutical effects and safety of use of fluvoxamine in women with major depression during the menopausal period. Subjects and methods: 31 women were enrolled to the trial. The age range was 43–64 years (mean 50±5). The criteria of ICD-10/DCR-10 were used to form study group. Only patients with major depression (single episode or recurrent depression) were taken into consideration. The following diagnostic tools and methods were used: –17 item version of HDRS, – Beck’s self-rating depression scale, – modified CGI Scale, – subjective evaluation of therapeutic effects (reported by patients), – inventory of adverse events reported spontaneously by patients. Subjects were evaluated on the baseline and after 1, 2, 4 and 6 weeks of active treatment. Fluvoxamine was given at a dose of 150 mg/day. Results: 1. The evaluation of the treatment results: – 30 patients reached the end-point of the trial 6 weeks observation. – In the study group, 56,8% reduction of HDRS score was found. A reduction of at least 50% was achieved in 19 respondents (61,3 %). 2. Evaluation of safety: After the first week, the most common complaint was nausea (50% of the study group). Also the stomach- and headache, tremor, dyspepsia were reported as adverse events with the frequency of 20–30% patients after the first week of treatment, but then it fall down to 0–5% (after week 6). The loss of appetite was observed at a level of 10–15% during the whole study. Conclusions: 1. After the use of fluvoxamine shows a good antidepressant effect was achieved. It is similar to that of other antidepressants from SSRI group. 2. In the majority of subjects, the tolerance of pharmacotherapy was evaluated as good. The highest number of adverse events was reported after the first week of treatment. At the end-point (after 6 weeks), the frequency of the adverse events decreased in most cases by 50 %, and in 7 out of 22 categories observed, it fell down to 0%.